The Abolition Of The Presidential Threshold From The Perspective Of Fikih Siyasah (A Study Of Constitutional Court Decision No. 62/Puu-Xxii/2024) - Yusrizal, Navis; Nuraini, Ririn (Hukum Islam, 2025)
This study examines whether Constitutional Court Decision No. 62/PUU-XXII/2024, which abolishes the presidential threshold for presidential and vice-presidential candidates, aligns with concepts in fiqh siyasah. Using qualitative library research and a descriptive-analytical method, the analysis applies the fiqh siyasah framework to assess the decision. The findings reveal that the abolition reflects the principle of al-Musawah—equality of rights for all citizens—an essential element in Islamic political thought. This concept includes both civil and constitutional rights, supporting inclusive political participation. The study also highlights scholarly views that the hadith restricting leadership to the Bani Quraish is no longer applicable. Therefore, the Court’s ruling aligns with Islamic jurisprudence, aiming to guarantee equal access to constitutional rights for all, without lineage-based restrictions. In conclusion, the decision mirrors the goals of fiqh siyasah by promoting equality and inclusivity within the democratic process in accordance with Islamic political values.